Analisis Pengaruh Brand, Harga, dan Prestise terhadap Keputusan Pembelian Smartphone Iphone di Sampit - Rahmawati, Nia (Universitas Darwan Ali, 2023)
The Analysis of The Impact of Brand, Price, and Prestige on the Purchase Decision of Iphone Smartphone in Sampit. This research method uses descriptive research methods with data collection techniques through questionnaires. Questionnaires with a Likert scale and questions about brand, price, prestige, and purchasing decisions are research instruments. The results showed that the Brand variable has a significance value of 0.080 > 0.05 and does not affect purchasing decisions. Thus Ho is approved while H1 is not approved. With a substantial value of 0.000 0.05, the price variable has a positive and significant effect on purchasing decisions. Thus Ha is approved while Ho is not approved. With a significance value of 0.003, the prestige variable has a favorable and significant influence on purchase choice. Thus Ha is approved while Ho is not approved.